Land use, planning, and the "difficult character of property". (3rd July 2017) - Blomley, Nicholas
Abstract: Contemporary land use planning has an ambivalent relationship with private property. While inextricably entangled with private property, planning frequently presents itself as at a remove, such that planning does not appear to regulate property, but rather acts upon "land use." It is tempting to see land use, therefore, as a means by which planning can institutionally distance itself from its necessary relationship to private property. An original genealogy of land use planning within Canada, however, reveals its entanglement with debates concerning the governance of land, and the imperative for the state assessment of the productive or wasteful uses to which it is put. Private property thus emerges as a central concern to planning, given its importance to landholding, the fear being that unregulated private property leads to unproductive and wasteful forms of land use . Viewed thus, land use should be treated not as the negation of property, but rather as a particular and constrained framing of the planning/property relationship. Put simply, land use asks certain questions of property, while eliding others. It becomes important, therefore, to open the "black box" of land use, in order to understand the important way in which planning practice engages private property.